Education and Social Change in Latin America - Motta, Sara C.; Cole, Mike.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book examines the multiple relationships between education, pedagogy, and social change in Latin America and beyond through a discussion of critical theory in education and its uses in Latin American society today. An international group of contributors discuss both individual countries and the region as a whole.
Keywords: Culture -- Study and teaching; Ethnology -- Latin America; Political theory; International education; Comparative education; Educational policy; ducation and state; Educational sociology; Education and sociology; Sociology, Educational; Cultural and Media Studies; Latin American Culture; Sociology of Education; International and Comparative Education; Political Theory; Educational Policy and Politics; Sociology of Education